Analysis of The Adoption of E-Commerce to Performance of Smes in Uganda - James Kamulindwa Muhumuza (Uganda Christian University, 2023)
This dissertation was conducted on the topic assessing the adoption of E-commerce by SMEs in Uganda. The study was commissioned by a fashion company called Kyaligonza, which is gradually integrating E-commerce into its operations, and it was guided by the following objectives: 1. To examine E Commerce adoption and performance by SMEs in Uganda; 2. To identify the benefits of E-commerce adoption to SMEs in Uganda; 3. To examine the barriers to E-commerce adoption by SMEs in Uganda. Data collection primarily relied on secondary sources, including journal articles, expert opinions, company reports, and newspapers. Additionally, questionnaires and document review checklists were used for data collection, providing a mix of qualitative and quantitative data. Ethical considerations were a priority, ensuring that data collection tools were designed with caution, avoiding personal questions unrelated to the study's purpose. The study focused on Kyaligonza Fashion Company, known for blending traditional Ugandan designs with modern silhouettes, catering to both local and international markets. Kyaligonza Fashion's adoption of e-commerce was driven by its desire to reach a global market, especially the Ugandan, Congolese, and diaspora niches. However, several barriers were identified, including limited internet access, low digital literacy among staff, challenges in online payment processing, and fierce market competition. Despite these barriers, the study revealed significant benefits of e-commerce adoption for Kyaligonza Fashion. These benefits included expanded market reach, 24/7 accessibility, reduced operating costs, and improved inventory management. These advantages contributed to the store's enhanced performance and competitive edge in the fashion industry. Overall, this research sheds light on the opportunities and challenges faced by SMEs in Uganda when embracing e-commerce, using Kyaligonza Fashion Company as a case study. It underscores the potential for growth and globalization through e-commerce adoption, while also highlighting the importance of addressing infrastructure and skill gaps to unlock its full potential.
This is a dissertation.